Measuring GDP at risk in the low-carbon transition - Dirk Schoenmaker; Willem Schramade (Bruegel, 2025)
As sustainability challenges push economies into low-carbon transitions, the question arises of what share of GDP is exposed to transition? We develop a two-stage model to examine the share of GDP facing transition risk. The first stage examines which sectors are directly exposed to transition(s) and the second stage assesses the transition preparedness of the exposed sectors. Applying this model to the energy transition in the European Union, we find that Sweden and France have low shares of GDP facing transition risk, while Poland and Bulgaria have high shares of GDP facing transition risk. The main driver is a country's carbon intensity, which we use as a proxy for transition preparedness. Our GDP-facing-transition risk model can inform policymaking. Countries can stimulate directed change towards low-carbon activities with a combination of taxes for high- carbon technologies and subsidies for low-carbon technologies. Moreover, countries can accelerate reallocation of labour towards low-carbon technologies and sectors by investing in education and retraining.
Keywords: 330